Outlander [compact disc, unabridged] - Gabaldon, Diana (Gabaldon, Diana. Outlander novels., 1997)
In 1945, a former combat nurse, back from the war and on her honeymoon, touches a boulder in an ancient Scottish ruin and is instantly transported to a Scotland torn by war and raiding border clans in 1743.